The flash crash: A review - Ali N. Akansu (Journal of Capital Markets Studies (JCMS), 2017)
Purpose - The purpose of this paper is to present an overview of the flash crash, and explain why and how it happened. Design/methodology/approach - The author summarizes several studies suggesting various perspectives on the flash crash and its causes. Furthermore, the author highlights recently proposed and introduced improvements and regulations to reduce the risk of having similar market collapses in the future. Findings - It is an overview paper that highlights the state of the art on the subject. Research limitations/implications - Paper does not report any research findings of the author. Practical implications - High-frequency trading (HFT) along with its pros and cons is the new normal for most of the current electronic trading activity in the markets. It is well recognized by the experts that HFT may have its important shortcomings whenever the rules and regulations are not up to date to match the technological progress offering faster computational and execution capabilities. Social implications - HFT has created a societal discussion about its benefits and potential deficiencies as the common practice for trading due to potentially unequal access to market data by various categories of participants. Such arguments help the regulators to develop improvements to reduce the market risk and nurture more robust and fair markets for all. Originality/value - The paper has a tutorial value and summarizes the current state of HFT. The readers of more interest are guided to the most relevant literature for further reading.
Keywords: 330; Algorithmic trading; Electronic trading; High-frequency trading (HFT); Limit order book (LOB); The flash crash; LOB imbalance; Security Information Processor (SIP); National best bid and offer (NBBO); Regulation national market system (Reg NMS); United States Securities and Exchange Commission (SEC)